An Investigation of Longitudinal Associations Between Psychological Distress and Student Victimization by Teachers. Issue 3 (February 2023) - Chen, Ji-Kang; Chang, Ching-Wen; Lin, Chung-Ying; Wang, Li-Chih
Previous research has suggested that psychological distress (i.e., anxiety, depression, and somatization) is associated with student victimization by teachers. The direction and causality of this relationship have not yet been empirically supported. This study examined longitudinal associations between adolescent psychological distress (anxiety, depression, and somatization) and student victimization by teachers among 419 adolescents in grades 7–9 of secondary schools in Hong Kong. A self-administered questionnaire was conducted to collect student self-reported information about their experiences of victimization by teachers and their psychological distress, including depression, anxiety, and somatization, at two time points separated by a 9-month interval. A cross-lagged panel analysis provided evidence for the contribution of depression, anxiety, and somatization to later victimization by teachers. These findings were also relevant for male and female adolescents. The findings suggest that psychological distress, such as depression, anxiety, and somatization, is a risk factor predicting student victimization by teachers rather than the consequences of exposure to teacher violence. The results support the importance of reducing adolescent depression, anxiety, and somatization symptoms in future intervention programs to prevent them from being victimized by teachers.